Structural stability of (Ga,M) As from first principles : Random alloys, ordered compounds, and superlattices (2006)
ABSTRACT: We calculate by a combination of density functional theory and mixed-basis cluster expansion the structural stability of ordered and disordered zincblende GaAs-MnAs systems. We find that the ground state of this system is phase separating into GaAs+MnAs, even though the strain energy is negligible. The study of short-period superlattices shows that the least-unstable superlattices are along the (111) orientation whereas the most-unstable orientation is the (201). The formation enthalpy of the random alloy has been calculated; combining it with a mean-field approximation, we obtain the temperature-composition phase diagram showing the miscibility-gap temperature below which the alloy phase separates (…).